Bjørnstjerne Bjørnson: En glemt dramatiker? - Marie Magnor (Teatervitenskapelige Studier)
The article explores why Bjørnstjerne Bjørnson (1832-1910) has largely been forgotten as a playwright in contemporary theatre by examining the reception history of his play Paul Lange and Tora Parsberg (1898). By analyzing a selection of theatre reviews from the play's Norwegian premiere in 1901 to its most recent staging in 2000, the article identifies and discusses the premises and criteria that have influenced theatre critics' evaluation of Bjørnson's drama over time. In the first half of the 20th century, critics assess the drama very positively, whereas from the 1980s onwards, critics tend to evaluate the play negatively while praising the staging. I argue that this devaluation of Bjørnson as a playwright is initially due to modernist expectations of what constitutes a good work of art, which has led critics around 2000 to view the drama mainly within the context of Bjørnson's status as a forgotten playwright.